La protección jurídica del derecho al honor en la corte superior de justicia de la libertad (2014 - 2016) - Mendocilla Ulloa, Edwin Yersson (2017)
The present investigation is to determine if the objective theory that dominates in the years 2014 to 2016 the jurisprudence of the Superior Court of Justice of La Libertad guarantees better the legal protection of the right to honor, has brought to light the issued sentences By the criminal courts of the Superior Court of Justice of La Libertad in the complaint process, with the objective of showing that it is the objective theory that has dominated the jurisprudence in the Court in mention, which becomes lacking of guarantee to The legal protection of the right to honor, since there is doctrinally a theory which would better guarantee the protection of the right to honor; Normative Fractional Theory. The investigation was carried out by means of the collection of the sentences issued by the single criminal courts of the Superior Court of Justice of La Libertad, which is constituted by a population of 42 sentences of which most of them are immersed by the Objective Theory , Being determined as effective for the legal protection of the right to honor, which through investigation in different doctrinal sources it is appreciated that the Normative-Theory proves to be the truly effective theory for the protection of the right to honor, consequently should be Theory That includes the jurisprudential content in the sentences in the processes of complaint issued by the single-criminal criminal courts of the Superior Court of Justice of La Libertad. As a result, it can be seen that of the 42 sentences issued in the lawsuit cases, 81% of the sentences mentioned are contained on the basis of the Theory of Failure, Theory that has been outdated in a Constitutional State of Law, which in merit To an effective legal protection of the right to honor is Normative Fractional Theory that should dominate the jurisprudential content in the sentences issued in the process Of complaint in the Superior Court of justice of La Libertad. In conclusion, opt for the Theory theory implies an impairment to the legal protection of the right to honor, implies Undue motivation of judicial decisions since it is Factual circumstances ignoring the constitutional rank that holds the right to honor. Theory-Normative Theory is the theory that is most effective for protection Of the right to honor in the establishment of special criminal Since it covers the factual aspect on which the subject is attached and the aspect Normative-constitutional basis on which the right to honor is found